Predicting Teachers’ Continuance Intention to Teach Online: The Role of Technostress, Intrapersonal and School Environmental Factors - Kai Wang; Zhenying Ye; Zhenyu Li; Shihua Li; Xue Yuan (SAGE Open)
As online teaching continues to be widely recognized and valued in global K–12 education, understanding the factors influencing teachers’ continuance intention is crucial, particularly in light of rising technostress. This study applied an extended COACTIV model to investigate how personal competencies and school environmental factors predict teachers’ intent to continue online teaching. Survey data from 573 in-service teachers in China were analyzed using structural equation modeling to assess relationships among key variables, including technological pedagogical content knowledge (TPACK), attitudes toward technology, teaching goal orientation, self-efficacy, teaching enthusiasm, resilience, technostress, administrative support, and workload. The findings reveal that while technostress and performance goal orientation negatively impact continuance intention, positive attitudes toward technology and robust administrative support enhance it. Moreover, teachers’ resilience, teaching goal orientation, and administrative support indirectly affect continuance intention by mediating technostress. These results provide valuable insights for improving the sustainability of online teaching practices in K–12 education.